Small finds - Dunn, Andrew (Scottish Archaeological Internet Reports, 2001)
A total of 48 small finds mostly derived from the fill of the great drain and the accompanying midden deposits. They included a silver spoon, silver and copper alloy pins, a coin, lace tags, needles, an iron spearhead and belt loop. There were also five fragments from a leather shoe and a number of rim sherds from glass vessels.